A comparison of three approaches for the discovery of novel tripartite attachment complex proteins in Trypanosoma brucei. - Hélène Clémentine Margareta Baudouin; Laura Pfeiffer; Torsten Ochsenreiter (Public Library of Science (PLoS), 2020)
Trypanosoma brucei is a single celled eukaryotic parasite and the causative agent of human African trypanosomiasis and nagana in cattle. Aside from its medical relevance, T. brucei has also been key to the discovery of several general biological principles including GPI-anchoring, RNA-editing and trans-splicing. The parasite contains a single mitochondrion with a singular genome. Recent studies have identified several molecular components of the mitochondrial genome segregation machinery (tripartite attachment complex, TAC), which connects the basal body of the flagellum to the mitochondrial DNA of T. brucei. The TAC component in closest proximity to the mitochondrial DNA is TAC102. Here we apply and compare three different approaches (proximity labelling, immunoprecipitation and yeast two-hybrid) to identify novel interactors of TAC102 and subsequently verify their localisation. Furthermore, we establish the direct interaction of TAC102 and p166 in the unilateral filaments of the TAC.